2011
DOI: 10.1038/emboj.2011.207
|View full text |Cite
|
Sign up to set email alerts
|

The functions of the actin nucleator Cobl in cellular morphogenesis critically depend on syndapin I

Abstract: Spatial control of cortical actin nucleation is indispensable for proper establishment and plasticity of cell morphology. Cobl is a novel WH2 domain-based actin nucleator. The cellular coordination of Cobl's nucleation activity, however, has remained elusive. Here, we reveal that Cobl's cellular functions are dependent on syndapin. Cobl/syndapin complexes form in vivo, as demonstrated by colocalization, coimmunoprecipitation and subcellular recruitment studies. In vitro reconstitutions and subcellular fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(123 citation statements)
references
References 35 publications
(84 reference statements)
2
119
0
2
Order By: Relevance
“…8, center top). This local destabilization of synaptic F-actin might be further enhanced by additional effects of reduced SdpI levels on the actin nucleator cordon bleu (48). In conclusion, SdpI could contribute to synaptic GlyR anchoring by regulating receptor immobilization via the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8, center top). This local destabilization of synaptic F-actin might be further enhanced by additional effects of reduced SdpI levels on the actin nucleator cordon bleu (48). In conclusion, SdpI could contribute to synaptic GlyR anchoring by regulating receptor immobilization via the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Localization of SdpI in Spinal Cord Neurons-So far, SdpI has been studied pre-and postsynaptically at excitatory synapses in rat hippocampus (24,48,49) and presynaptically at the reticulospinal synapse in lamprey (19). Additionally, SdpI has been found in parvalbumin-positive inhibitory interneurons of the mouse brain (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SH3-domain-mediated interactions of syndapin I have been shown to play a pivotal role in the recruitment of cellular machineries involved in endocytic vesicle formation and actin nucleation (Schwintzer et al, 2011) to the plasma membrane. Furthermore, biochemical studies have demonstrated that, at least in the case of syndapin I, its SH3-domain-interaction partners can be incorporated into larger protein complexes that arise from self-association of syndapin F-BAR domains (Kessels and Qualmann, 2006;Schwintzer et al, 2011) (Fig. 3B).…”
Section: The Power Of Physical Integrationmentioning
confidence: 99%
“…Morphometric measurements of transiently transfected hippocampal neurons were performed with ImageJ according to Schwintzer et al (2011). Transfected neurons identified by anti-MAP2 staining were imaged in systematic sweeps across the cover slips of repeated transfections with independent neuronal preparations.…”
Section: Immunofluorescencementioning
confidence: 99%